Effectiveness of Video Media and Prezi Software in the VAK Learning Model to Enhance Science Process Skills of Elementary Students - Amrullah, Ridwan (Elementary Education Journal, 2024)
Background: Science Process Skills (KPS) are crucial in preparing students to meet the challenges of the 4.0 industrial era, emphasizing critical thinking and scientific reasoning from an early age. However, conventional teaching methods without adequate media assistance often result in passive learning environments. Innovative teaching models supported by appropriate media are essential to enhance students' scientific competencies. Objective: This study aims to compare the effectiveness of the Visualization, Auditory, Kinesthetic (VAK) learning model assisted by video media and Prezi software on improving the science process skills of fifth-grade students at MIM PK Kartasura. Method: A quasi-experimental design with a nonequivalent pretest-posttest control group was used. The sample consisted of 55 fifth-grade students, divided into two experimental groups: one group was treated with Prezi software, and the other with video media. Data were collected through tests validated for content and construct validity and analyzed using prerequisite tests (normality and homogeneity) followed by hypothesis testing with paired sample t-tests and independent sample t-tests. Results: The findings revealed significant improvements in students’ science process skills in both groups after the interventions. However, the video media group showed a higher increase in average scores compared to the Prezi software group. Statistical analysis indicated that video media was more effective than Prezi software in enhancing students' science process skills. Conclusion: The VAK learning model assisted by video media proved to be more effective in developing the science process skills of elementary students compared to the use of Prezi software. The results suggest that integrating video media into science instruction can significantly enhance critical learning competencies, serving as a valuable reference for educators in designing engaging and effective learning environments.